Low progesterone receptor levels in high-grade DCIS correlate with HER2 upregulation and the presence of invasive components - Schandiz, Hossein; Farkas, Lorant; Park, Daehoon; Liu, Yan; Andersen, Solveig N.; Geisler, Jürgen; Sauer, Torill (Frontiers in Oncology, 2024)
Objective In this study, we investigated pivotal molecular markers in human high-grade breast ductal carcinoma in situ (DCIS). Expression status of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth receptor 2 (HER2) was measured among various subtypes (Luminal (Lum) A, LumB HER2-, LumB HER2+, HER2-enriched and triple-negative). Methods In total, 357 DCIS cases were classified into respective subtypes, according to the 2013 St. Gallen guidelines. Each subtype was categorized into three subcategories: “Pure” (those without an invasive component), “W/invasive” (those with an invasive component), and “All” (the entire group of the given subtype). ER and PR expression were registered as intervals. Equivocal HER2 immunohistochemistry (IHC) cases (2+) were further investigated using dual-color in situ hybridization. Results The majority of patients (71%) were over the age of 50. We discovered no significant differences in the proportion of age between the “Pure” and “W/invasive” groups. There was no significant difference in ER/PR expression between “Pure” luminal subtypes of DCIS and “W/invasive” cases. We compared the HER2 IHC scores of “0”, “1+”, and “2+” among LumA and LumB HER2 subtypes and identified no statistically significant differences between “Pure” and “W/invasive” (p = 0.603). ER and PR expression ≥ 50% cutoff value was present in > 90% of all LumA cases. The incidences of cases with ER expression at cutoff values of < 10% and ≥ 50% in LumA were significantly different compared to other luminal subtypes (p < 0.0001). The proportion of cases with PR expression < 20% showed significant differences in the various luminal subtypes. In luminal B subtypes, low PR expression (< 20%) was significantly associated with both strong HER2 expression (3+) and the presence of an invasive component (p = 0.0001 and p = 0.0365, respectively). Conclusions ER and PR expression at ≥ 50% cutoff values were found in more than 90% of LumA cases. Samples with ER < 10% and ≥ 50% in LumA were significantly different compared to other luminal subtypes (p < 0.0001). Low PR expression in high-grade DCIS was strongly associated with HER2 overexpression (3+) and an invasive component (p = 0.0001 and p = 0.0365, respectively).